ANALISIS KEKUATAN TARIK SAMBUNGAN PLAT ALUMINIUM AA 5083 PADA PADA PROSES SPOT WELDING - Sobron Yamin Lubis; Sofyan Djamil; Rosehan Rosehan; Harley Anugrah; Kevin Raynaldo (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
Spot welding is a method of electrical resistance welding in which two or more metal sheets are clamped between two electrodes and at the same time an electric current is applied so that the surface of the material reaches the welding temperature and then the material is fused. The purpose of the study was to determine the tensile strength of the 5083 aluminum plate connection in the spot welding process. This research was carried out experimentally as for the plate material that is connected is aluminum AA 5083 which has a thickness of 1 mm. Before welding is carried out, it is necessary to determine the variation of parameters, namely the welding current of 1.75 volts, 2.20 volts, 2.28 volts and the welding time for 1 second, 1.5 seconds, and 2 seconds. The spot welding process is carried out by varying these parameters, with the shape of the connection that occurs is overlapping. After the splicing process, then the specimen is tested for connection strength through a tensile. From the results of the study, it was obtained that the greater the electric current used, the greater the electric power used and it can be seen that the longer the welding time, the greater the electric power used. Keywords: Spot welding, tensile strength, AA 5083. aluminum Abstrak Las titik (spot welding) merupakan salah satu cara pengelasan resistansi listrik di mana dua atau lebih lembaran logam di jepit di antara dua elektroda dan pada saat yang bersamaan arus listrik di alirkan sehingga permukaan material mencapai temperatur pengelasan kemudian material bersatu. Penelitian di laksanakan bertujuan untuk mengetahui kekuatan tarik sambungan plat alumunium 5083 pada proses spot welding. Penelitian di lakukan secara eksperimen, adapun bahan plat yang di sambung adalah aluminium AA 5083 yang memiliki ketebalan 1 mm. Sebelum pengelasan di lakukan, maka di tentukan terlebih dahulu variasi parameter yaitu arus pengelasan yang terdiri dari 1,75 V, 2,20 V, 2,28 V dan waktu pengelasan selama 1 s, 1,5 s, 2 s. Proses spot welding di lakukan memvariasikan parameter tersebut, dengan bentuk sambungan adalah tumpang tindih. setelah proses penyambungan, kemudian spesimen di lakukan pengujian kekuatan sambungan melalui uji tarik.Hasil penelitian di peroleh bahwa jika tegangan arus listrik semakin besar di gunakan, maka semakin besar daya listriknya, dan semakin lama waktu pengelasan maka daya listrik yang di gunakan semakin besar.